Navigating The Flow of Challenges: Problematics of Implementing Kurikulum Merdeka in Sociological Subject at SMAN 1 Tumpang - Malang - Dini, Alya Muflihatud; Fibrianto, Alan Sigit; Huda, Ahmad Tirtho Faidl; Azzahra, Annisa Shafa; Cempaka, Lutfia; Muna, Nabila Nasywal; Lestari, Nia; Titis, Titis (Jurnal Sosiologi Pendidikan Humanis, 2023)
The Merdeka Curriculum aims to empower students with a more independent and innovative learning approach. However, the process of implementing the Independent Curriculum in sociology learning at SMAN 1 Tumpang was faced with several problems. This article aims to identify and analyze the challenges, difficulties, solutions, and strategies for implementing the Merdeka curriculum in the context of learning sociology at SMAN 1 Tumpang. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The research subjects were selected using a purposive sampling technique, namely one of the Sociology teachers at SMAN 1 Tumpang who was involved in the learning process and school staff related to implementing the independent curriculum. The study results show that implementing the independent curriculum at SMAN 1 Tumpang brings several challenges that require the active role of educators in identifying the needs and abilities of individual students. Making teaching modules, teacher difficulties in implementing P5, and learning administration. In dealing with these difficulties, the Sociology teacher at SMAN 1 Tumpang took various strategic solutions, such as integrating technology in education, providing training and coaching to teachers, and creating collaboration between teachers and students.Menavigasi Arus Tantangan : Problematika Pengimplementasian Kurikulum Merdeka dalam Pembelajaran Sosiologi di SMAN 1 Tumpang - MalangKurikulum Merdeka bertujuan untuk memberdayakan peserta didik dengan pendekatan pembelajaran yang lebih mandiri dan inovatif. Namun, proses implementasi Kurikulum Merdeka dalam pembelajaran sosiologi di SMAN 1 Tumpang dihadapkan pada sejumlah problematika. Artikel ini bertujuan untuk mengidentifikasi dan menganalisis tantangan, kesulitan, solusi dan strategi penerapan kurikulum Merdeka dalam konteks pembelajaran sosiologi di SMAN 1 Tumpang. Metode yang digunakan adalah metode penelitian kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Subjek penelitian dipilih menggunakan teknik purposive sampling yaitu salah satu guru Sosiologi SMAN 1 Tumpang yang terlibat dalam proses pembelajaran dan staf sekolah yang terkait dengan implementasi kurikulum merdeka. Hasil dari penelitian menunjukkan bahwa Implementasi kurikulum merdeka di SMAN 1 Tumpang membawa sejumlah tantangan yang memerlukan peran aktif tenaga pendidik dalam mengidentifikasi kebutuhan dan kemampuan siswa secara individual, tidak hanya itu berbagai kesulitan juga muncul diantaranya yaitu sulit mengubah kebiasaan siswa yang dituntut belajar mandiri, kesulitan dalam pembuatan modul ajar, kesulitan guru dalam penerapan P5, serta kesulitan dalam melakukan administrasi pembelajaran. Dalam menghadapi berbagai kesulitan tersebut, guru Sosiologi SMAN 1 Tumpang mengambil berbagai solusi strategis, seperti mengintegrasikan teknologi dalam pembelajaran, memberikan pelatihan dan pembinaan kepada guru, dan menciptakan kolaborasi antara guru dan siswa.